Pengaruh Penambahan Kinesio Taping Pada Terapi LowBack Pain Myogenic Terhadap Peningkatan AktivitasFungsional Di Rsu Ade Muhammad Djoen Sintang - Arline, Arline; , Wahyuni, S.KM, S.Fis, M.Kes (2016)
BACKGROUND: low back pain is the feeling of the myogenic musculoskeletal pain in the region of lumbosakral and sakroiliaka. Disability or limitation in conducting a functional daily activity. Modalities can be used one is conventional therapy on kinesio taping with add to help process the pain reduction was finally able to oversome the problem of disability. OBJECTIVE: to know the influence of addition of kinesio taping on the therapy of low back pain myogenic to increased activity of functional. RESEARCH METHODOLOGY: the study using a research method of Quasi Experiment or quasi experiment is a research by conducting the experiment (exsperimen) that aims to find out the symptoms or influence arising, as a result of the existence of a particular treatment or experiment. In this study the author uses the method with pre test and post test. RESULTS: the data obtained is not gaussian, statistical tests using Wilcoxon testtest to know the disability pre and post test-test on the group by giving preferential treatment to coventional therapy and the addition of kinesio taping, obtained a value 1.000 P and P or value of 0.005 < 0.05 so group A and group B rejected Ha, Ha is accepted which means no influence awarding of conventional therapies and there is the influence of the addition og kinesio taping improved the functional activity of low back pain myogenic and Mann Whitney test knowing the difference of influence conventional therapy treatment with the addition of kinesio taping, the retrieved value P: 0.014 or value P < 0.05 Ha so accepted, which means there are different granting conventional therapies influence with the addition of kinesio taping which written more effectively to the increased functional activity of low back pain myogenic. CONCLUSION: can be concluded that there are differences in the effect of conventional therapy with the addition of kinesio taping to the increase of the functional activity of low back pain myogenic.